Modern input promotion in Africa: Overview of evidence and future policy direction - Rashid, Shahidur; Jayne, Thomas S.; Minot, Nicholas (International Food Policy Research Institute, 2014)
The case for enhancing agricultural productivity through promotion of modern inputs is fairly easy to make. Promoting input use and intensifying agriculture, however, have proved difficult for most African countries under a wide range of policy initiatives since 1970s, ranging from universal subsidy, market liberalization, to smart subsidies in recent years. The central objective of this paper is to highlight the evolving policy options and, to do so, we analyze the trends in fertilizer and seed use and synthesize the evidence on the impacts of modern input promotion policies.